Protection of Women's Rights in Islamic Family Law: A Review of Jurisprudence and Legislation in Indonesia - Harun Al-Rasyid (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This article provides a comprehensive review of the protection of women's rights within the framework of Islamic Family Law (IFL) in Indonesia. The study examines the historical development of IFL, its interaction with national legislation, and the jurisprudence of the Religious Courts. The research employs a qualitative approach, analyzing relevant legal documents, scholarly articles, and court decisions. The findings reveal a complex interplay of religious interpretations, cultural norms, and legal reforms. While significant progress has been made in recognizing and protecting women's rights, challenges persist due to patriarchal interpretations, societal biases, and the influence of conservative groups. The article highlights the role of legal support structures, women's movements, and progressive interpretations of Islamic texts in advocating for gender equality. It also explores the impact of legal reforms on issues such as marriage, divorce, inheritance, and child custody. The conclusion underscores the need for continued efforts to ensure that IFL aligns with principles of justice, equality, and human rights, emphasizing the importance of legislative reform, judicial activism, and community engagement to empower women and promote their well-being.